Screening for Depression in Adolescents in Gokarneshwor Municipality-4, Kathmandu - Shrestha, Niraj; Pandey, S (Nepal Medical College Journal, 2019)
Depression which is characterized by hopelessness and loss of interest in social activities is common during adolescence. However it is often unrecognized and the burden is even more in low income countries. It also increases the risk of suicide in future. Hence in a developing country like Nepal it is important that such cases are detected at the early stage preventing further worsening of the condition. A simple set of questionnaires like Patient Health Questionnaire (PHQ) 9 can be used to screen for depression. Using this questionnaire screening for depression was carried out in adolescents of Gokarneshwor municipality, ward 4. Four hundred and twenty participants were selected by the process of systematic random sampling. Based on answers to nine questions score was given and adolescents categorized as having no, mild, moderate or severe depression. The PHQ 9 score suggested that 13.1% were suffering from depression, out of which 23.6% from moderate to severe depression which required psychiatric consultation. Out of those shown to have some form of depression 40.0% said they had thought of self harm in last 2 weeks. Late adolescence was significantly associated with depression. Thoughts related to self harm were also six times more in late adolescent age group than the early adolescent age group.